Prognostic value of positive lymph node ratio in oral cavity squamous cell carcinoma after neoadjuvant treatment: a retrospective real-world study - Sufeng Fan; Shunv Cai; Yun Cheng; Yimin Wu; Wenmei Jiang (Scientific Reports)
Abstract This study aimed to address the prognostic value of positive lymph node ratio for oral cavity squamous cell carcinoma (OCSCC) patients after neoadjuvant treatment, and build a prediction nomogram model. Patients with OCSCC with neoadjuvant treatment were retrieved from the Surveillance, Epidemiology, and End Results database from 2004 to 2021. The primary outcome was overall survival (OS), and the second outcome was disease-specific survival (DSS). Kaplan–Meier and log-rank tests were used to analyze the survival outcomes. Univariable and multivariable analyses were conducted, and then a nomogram was constructed. A total of 419 were included in this study. The optimal cutoff value of the positive lymph node ratio (LNR) was 7.0%. The 5-year OS of patients with low LNR was significantly improved over those with high LNR (p < 0.0001). LNR > 7.0% (HR 50.7, 95% CI 19.7–130.5), and unmarried status (HR 1.33, 95% CI 1.03–1.70) were the independent risk factors for OS (all p < 0.05). LNR > 7.0% (HR 35.8, 95% CI 9.63–132.7), gum primary site (HR 0.330, 95% CI 0.132–0.827), and preoperative chemotherapy and radiotherapy (HR 2.91, 95% CI 1.78–4.73) were the independent risk factors for DSS (all p < 0.05). According to the nomogram, patients were stratified into the high-risk group and the low-risk group for OS and DSS. Patients in the low-risk group were predicted with superior survival (both p < 0.05). The LNR was an independent prognostic factor of the OS and DSS for OCSCC patients after neoadjuvant treatment. The tools may be valuable to guide multidisciplinary teams in making treatment decisions.